[PP.19.15] RETINAL ARTERIOLES HYPERTROPHIC REMODELING IN UNCONTROLLED ACROMEGALY. (September 2017) - Gallo, A.; Kassasseya, E.; Mattina, A.; Bruckert, E.; Girerd, X.; Jublanc, C.; Rosenbaum, D.
Abstract : Objective: Acromegaly is characterized by an increased cardiovascular risk. Hypertrophic effects of Growth Hormone (GH)/Insulin-like Growth Factor 1 (IGF1) system on the heart and large arteries are known but little data on microcirculation exist. Our aim was to assess retinal arteriolar remodeling in acromegaly patients using adaptive optics camera. Design and method: Adaptive Optics RTX1® Camera (ImagineEye, Orsay, France) was used to measure Wall Thickness (WT), Internal Diameter (ID) and to calculate Wall Cross Sectional Area (WCSA) and Wall-to-Lumen Ratio (WLR) on retinal arterioles of patients with acromegaly. As IGF1 is gender and age-dependent, an IGF1/normal value ratio (IGF1r) was generated for each patient. Acromegaly patients were then stratified according to their IGF1r: patients with IGF1r> = 1 were defined as uncontrolled, patients with IGF1r<1 were defined as having controlled acromegaly. Moreover, non-acromegaly control subjects matched for age/gender/diabetes/blood pressure levels and antihypertensive treatments were also recruited. Results: 80 patients and controls were recruited. Mean age was 51 ± 12 years and 54% were men. Subjects with uncontrolled acromegaly exhibited hypertrophic remodeling with increased WLR, WT and WCSA compared to both controlled patients and control subjects (Table). Figure. No caption available. No differences in ID were found between controls and patients with controlled acromegaly. Mean IGF1r was higher in uncontrolled subjects compared to subjects with controlled acromegaly (1.3 ± 0.46 vs 0.72 ± 0.18, p < 0.001). Moreover, IGF1r value was positively associated to WLR (r 2 = 0.3, p < 000.1) and negatively to lumen (r 2 = 0.1, p = 0.02) while there was a trend towards a positive association with WCSA and WT. Conclusions: Subjects with uncontrolled acromegaly exhibit hypertrophic arteriolar retinal remodeling associated with IGF1 levels increase. Normal retinal arteriolar anatomy has been found in patients with a controlled disease suggesting a potential reverse remodeling under treatment.